1988
DOI: 10.1017/s0317167100027785
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Atrophy in Epileptic Patients

Abstract: High-resolution CT scans of the brain and posterior fossa were performed on 106 phenytoin (PHT)treated epileptics, 28 de novo epileptics and 43 control subjects. A higher incidence of cerebellar and brainstem (CBS) atrophy was observed in chronic PHT-or PHT+ phenobarbital-treated epileptics compared to the two other groups. Some control subjects and de novo epileptics presented mild CBS atrophy, whereas moderate to severe atrophy was noted exclusively in chronically-treated patients. In attempting to delineate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
4

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 22 publications
2
27
0
4
Order By: Relevance
“…Embora haja relatos na literatura [1][2][3][4][5][6][7][8][9][10] de ataxia permanente associada ao uso de fenitoína em altas doses e por tempo prolongado, existem poucos estudos com casuística suficiente para definir a etiologia da atrofia cerebelar. O estabelecimento de correlação inequívoca entre o uso de fenitoína e a atrofia cerebelar é difícil pois, na maioria dos casos, além do uso da medicação anticonvulsivante, os pacientes também apresentam crises tônico-clônicas generalizadas e hipóxia decorrente destas crises.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Embora haja relatos na literatura [1][2][3][4][5][6][7][8][9][10] de ataxia permanente associada ao uso de fenitoína em altas doses e por tempo prolongado, existem poucos estudos com casuística suficiente para definir a etiologia da atrofia cerebelar. O estabelecimento de correlação inequívoca entre o uso de fenitoína e a atrofia cerebelar é difícil pois, na maioria dos casos, além do uso da medicação anticonvulsivante, os pacientes também apresentam crises tônico-clônicas generalizadas e hipóxia decorrente destas crises.…”
Section: Discussionunclassified
“…Rapport & Shaw 4 estabeleceram com maior segurança a relação entre fenitoína e atrofia cerebelar ao relatar este achado em um paciente tratado profilaticamente com fenitoína e que nunca havia apresentado crise epiléptica. Entretanto, colaboram para a controvérsia dos estudos 3,8 que demonstram ser a hipóxia, devida às crises generalizadas frequentes, uma provável causa de lesão cerebelar.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…An additional important issue is evidence that phenytoin can exert toxic effects on the cerebellum in patients with epilepsy 32 ; the toxicity is associated with ataxia, tremor, nystagmus and diplopia 32,33 . Furthermore, cerebellar atrophy can occur in phenytoin-exposed patients with epilepsy in the absence of generalised tonicclonic seizures or pre-existent brain damage 32,34,35 . Since the child evaluated in our study did not use phenytoin in his antiepileptic drug therapy schedule, our research group did not consider this issue.…”
Section: Brain Regions and Sudepmentioning
confidence: 99%
“…Specht and colleagues demonstrated in 1997 that cerebellar atrophy diagnosed by MRI was a frequent finding in surgically treated patients with temporal lobe epilepsy 44 , and concluded that increased age, presence of generalized seizures, and intellectual disability were the principal factors associated with cerebellar volume losses in their patients 44 . Botez and co-workers studied 134 adult patients with epilepsy using high-resolution CT scans, and found a higher incidence of cerebellar atrophy with longer duration of epilepsy and treatment with phenytoin 48 . Convincing evidence exists that prolonged phenytoin use, or a single episode of phenytoin intoxication can elicit severe and irreversible cerebellar atrophy 42,44,49,50 .…”
Section: Cerebellar and Autonomic Processmentioning
confidence: 99%